Projecting the global potential distribution of nine Rhododendron Subgenus Hymenanthes species under different climate change scenarios - Qian Ao; Huie Li; Lan Yang; Qian Li; Fenfang Long; Yang Xiao; Weiwei Zuo (Scientific Reports)
Abstract As one of China’s most treasured traditional flowers, Rhododendron Subgen. Hymenanthes is renowned worldwide for its evergreen foliage, vibrant flowers, and significant ornamental, landscaping, and economic value. However, climate change poses a serious threat to its future, leading to population declines and endangerment of some species. Despite the ecological and economic importance of Rhododendron Subgen. Hymenanthes, the future distribution of suitable habitats and the most effective strategies for its conservation and utilization remain unclear. This study employs the MaxEnt model, which is well-known for its reliability in predicting species distribution under changing environmental conditions, to predict the potential global distribution of nine species of Rhododendron Subgen. Hymenanthes. The goal is to provide a solid foundation for their conservation, cultivation management, and breeding. The results indicate that, under future climate scenarios, suitable habitat areas for four species (R. irroratum, R. agastum, R. decorum, and R. arboreum) will significantly decrease, while suitable habitats for the remaining five species (R. delavayi, R. fortunei, R. calophytum, R. simiarum, and R. wardii) will experience slight expansion. Temperature and precipitation are identified as key environmental factors influencing the growth and distribution of these species, affecting their ability to colonize new regions. The migration direction of the expanding regions for all nine species is consistent, with their centroids shifting towards the northwest. These findings provide critical insights for developing targeted conservation strategies, including identifying potential refugia and prioritizing conservation areas under future climate conditions.